Role of bulge epidermal stem cells and TSLP signaling in psoriasis - Nuria Gago‐Lopez; Liliana F Mellor; Diego Megías; Guillermo Martín‐Serrano; Ander Izeta; Francisco Jimenez; Erwin F Wagner (EMBO Molecular Medicine, 2019)
Abstract Psoriasis is a common inflammatory skin disease involving a cross‐talk between epidermal and immune cells. The role of specific epidermal stem cell populations, including hair follicle stem cells (HF‐SCs) in psoriasis is not well defined. Here, we show reduced expression of c‐JUN and JUNB in bulge HF‐SCs in patients with scalp psoriasis. Using lineage tracing in mouse models of skin inflammation with inducible deletion of c‐Jun and JunB, we found that mutant bulge HF‐SCs initiate epidermal hyperplasia and skin inflammation. Mechanistically, thymic stromal lymphopoietin (TSLP) was identified in mutant cells as a paracrine factor stimulating proliferation of neighboring non‐mutant epidermal cells, while mutant inter‐follicular epidermal (IFE) cells are lost over time. Blocking TSLP in psoriasis‐like mice reduced skin inflammation and decreased epidermal proliferation, VEGFα expression, and STAT5 activation. These findings unravel distinct roles of HF‐SCs and IFE cells in inflammatory skin disease and provide novel mechanistic insights into epidermal cell interactions in inflammation.